An Evaluation of the Impact of the Amount of Potassium Hydroxide on the Porous Structure Development of Activated Carbons - Kwiatkowski, Mirosław (Materials (Basel), 2021)
This paper presents the results of an evaluation of the impact of the amount of potassium hydroxide on the obtained porous structure of the activated carbons derived from the shells of pistachios, hazelnuts, and pecans by carbonization and subsequent chemical activation with potassium hydroxide by different adsorption methods: Brunauer–Emmett–Teller, Dubinin–Raduskevich, the new numerical clustering-based adsorption analysis, Quenched Solid Density Functional Theory, and 2D-Non-linear Density Functional Theory for Heterogeneous Surfaces, applied to nitrogen adsorption isotherms at −196 °C. Based on the conducted research, a significant potential for the production of activated carbons from waste materials, such as nut shells, has been demonstrated. All the activated carbons obtained in the present study at the activator/char mass ratio R = 4 exhibited the most developed porous structure, and thus very good adsorption properties. However, activated carbons obtained from pecan shells deserve special attention, as they were characterized by the most homogeneous surface among all the samples analyzed, i.e., by a very desirable feature in most adsorption processes. The paper demonstrates the necessity of using different methods to analyze the porous structure of activated carbons in order to obtain a complete picture of the studied texture. This is because only a full spectrum of information allows for correctly selecting the appropriate technology and conditions for the production of activated carbons dedicated to specific industrial applications. As shown in this work, relying only on the simplest methods of adsorption isotherm analysis can lead to erroneous conclusions due to lack of complete information on the analyzed porous structure. This work thus also explains how and why the usual characterizations of the porous structure of activated carbons derived from lignocellulosic biomass should not be taken at face value. On the contrary, it is advisable to cross reference several models to get a precise idea of the adsorbent properties of these materials, and therefore to propose the most suitable production technology, as well as the conditions of the preparation process.